Sex Differences in Virtual Network Characteristics and Sexual Risk Behavior Among Emerging Adults. (August 2016) - Cook, Stephanie H.; Bauermeister, José A.; Zimmerman, Marc A.
Emerging adults (EAs) aged 18–24 account for a large proportion of all sexually transmitted infections (STIs), HIV infections, and unintended pregnancies in the United States. Given the increased influence of online media on decision making, we examined how EA online networks were associated with sexual risk behaviors. We used egocentric network data collected from EAs aged 18–24 years old across the United States ( N = 1, 687) to examine how online social norms (e.g., acceptance of HIV infections, other STIs, and pregnancy) and network characteristics (i.e., network size and density; ties' closeness, race, age, and sex similarities) were associated with participants' unprotected vaginal intercourse in the last 30 days. Findings suggested that in male EAs, there was a strong association between online social norms, structural characteristics, and sexual risk behavior compared to females. Researchers and practitioners may wish to address online peer norms and EAs' online network composition when developing online sexual risk prevention tools.